2016
DOI: 10.1038/leu.2016.271
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies risk loci for childhood acute lymphoblastic leukemia at 10q26.13 and 12q23.1

Abstract: Genome-wide association studies (GWASs) have shown that common genetic variation contributes to the heritable risk of childhood acute lymphoblastic leukemia (ALL). To identify new susceptibility loci for the largest subtype of ALL, B-cell precursor ALL (BCP-ALL), we conducted a meta-analysis of two GWASs with imputation using 1000 Genomes and UK10K Project data as reference (totaling 1658 cases and 7224 controls). After genotyping an additional 2525 cases and 3575 controls, we identify new susceptibility loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 55 publications
3
72
0
Order By: Relevance
“…Among the E/R+ TF network, ELK3 and SP4 have been reported to confer risk of leukemia development in GWAS studies [48,49]. Previous expression quantitative trait loci data from mature B lymphoid cells indicated that the ELK3 risk variant associates with its lower expression [48]. This contrasts the data obtained here where high expression was seen in E/R+ scRNA-seq data, which we confirmed by bulk gene expression data comparing across hematologic malignancies [50].…”
Section: Single Cell Profiling Techniques Have Challenged How We Defisupporting
confidence: 71%
See 2 more Smart Citations
“…Among the E/R+ TF network, ELK3 and SP4 have been reported to confer risk of leukemia development in GWAS studies [48,49]. Previous expression quantitative trait loci data from mature B lymphoid cells indicated that the ELK3 risk variant associates with its lower expression [48]. This contrasts the data obtained here where high expression was seen in E/R+ scRNA-seq data, which we confirmed by bulk gene expression data comparing across hematologic malignancies [50].…”
Section: Single Cell Profiling Techniques Have Challenged How We Defisupporting
confidence: 71%
“…5a) across a large microarray gene expression dataset [50] (Hemap, N=9544, with 1304 pre-B-ALL samples). The ETS-factor ELK3 and SP4 have been implicated by genome-wide association (GWAS) studies as risk loci for pediatric pre-B-ALL [48,49]. Based on the bulk transcriptomes, we could validated both to be expressed in B-ALL, with highest proportion detected in the E/R+ subtype (red arrow), as shown comparing hematologic malignancies on the t-SNE plot of Hemap samples ( Fig.…”
Section: The Leukemic Regulatory Program Reveals Cell State Infidelitmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly in children the CRLF2/IL7RA subtype occurs later than the other genotypic subtypes of ALL 65 . Recently, gene-wide association studies have discovered several relatively common SNPs conferring a higher risk for childhood ALL 45,47,52,[66][67][68] . Strikingly, the genotype of the specific CB the transduction of which resulted in BCP-ALL, revealed heterozygosity for five predisposing SNPs scattered across four of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies have identified common genetic variants associated with ALL risk. [2][3][4][5][6][7][8] Recent studies of familial ALL have revealed rare predisposing germline mutations in the hematopoietic regulator genes PAX5, SH2B3, ETV6, and IKZF1, [9][10][11][12][13][14][15] and next-generation sequencing in large numbers of de novo childhood ALL patients has identified at least 4% with likely functional germline mutations. 16,17 Elucidating the genetic component of ALL will be essential for risk stratification, prevention, and early detection of disease.…”
Section: Introductionmentioning
confidence: 99%